KUALITAS PELAYANAN ADMINISTRASI PADA PASIEN BPJS DI RUMAH SAKIT UMUM DAERAH KABUPATEN ROKAN HULU - Vivi Winda Putri; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The research was conducted at the Home Sick General Area of Distric Rokan Hulu, with the aim of knowing the quality of administrative service for BPJS patients at Home Sick General Area of Rokan Hulu and to find out what are the factors that hinder the quality of administrative services at Home Sick General Area of Rokan Hulu. The problem of this research is the administration of Home Sick General Area of Rokan Hulu administration carried out by home sick employees in the process of providing services to the community, there are still service providers who are stalling for time so that the administration is not carried out time and results in less than optimal services so that people lose their trust in public serviceproviders. This is mostly prevalent in BPJS patients. Selection of informants using purposive sampling technique with data collection technique include: observation, interview, and documentation. The results of the study indicate that the quality of administrative services for BPJS patients in Home Sick General Area of Rokan Hulu is still not optimal, administrative services for BPJS patients at Home Sick General Area of Rokan Hulu are still not optimal, this is because there are still employees who do not understand how to operate computers properly so that the data input process is still late in the predetermined time even though the rumah sakit employees have received training. The attitude of employees in providing services is still not maximal in providing services to BPJS patients. There are still differences between BPJS and general patients, especially when waiting for the queue for treatment. Therefor, the community uses the rumah sakit services more than the home sick swasta belonging to the area.Key word: Quality service , BPJS Health , Home Sick